(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The present article will approach the so called CNJ, created by the 45/2004 amendment and displayed on article 103-B of our Constitution, and its relation and limits with notaries and their extra judicial offices, that are defined on article 236 of the Constitution, being managed by delegation of Public authorities.